Interest of the Sharia Insurance Community in Prudential Syariah Binjai - Indah Simanjuntak; Fauzi Arif Lubis (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Sharia insurance is one form of Islam's role in building community welfare by providing diversity and forms of cooperation in financing and financial management. Islamic insurance which is in line with the teachings of Islam. There are also new innovations that cannot be separated from maysir gharar and usury.